1965
DOI: 10.1037/h0022496
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of test anxiety and hostility to description of self and parents.

Abstract: Questionnaire-assessed test anxiety and hostility were related to the verbal productions of male and female college students. Each S's task was to describe himself, and his mother and father. These descriptions were content analyzed for positive and negative evaluations of self and parents. Test anxiety was found to be related to the incidence of negative self-references, but not to negative references to parents. Hostility was found to be unrelated to selfreferences. Fewer positive references were emitted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1968
1968
2008
2008

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Mueller and Thompson (1984) also found that high test-anxious individuals showed a negative bias in their self-concept in accepting more negative adjectives as self-descriptive. Wine (1971) also concluded from her review of I. G. Sarason's early experimental studies Ganzer 1962, 1963;Sarason and Koenig 1965) that high test-anxious individuals generally describe themselves in more negative terms than do low test-anxious individuals. Hence, we would also expect Beck's cognitive triad to be related to debilitating test anxiety (Hypothesis 1b).…”
Section: The Present Studymentioning
confidence: 91%
“…Mueller and Thompson (1984) also found that high test-anxious individuals showed a negative bias in their self-concept in accepting more negative adjectives as self-descriptive. Wine (1971) also concluded from her review of I. G. Sarason's early experimental studies Ganzer 1962, 1963;Sarason and Koenig 1965) that high test-anxious individuals generally describe themselves in more negative terms than do low test-anxious individuals. Hence, we would also expect Beck's cognitive triad to be related to debilitating test anxiety (Hypothesis 1b).…”
Section: The Present Studymentioning
confidence: 91%
“…These task-irrelevant thoughts often involve excessive preoccupation with negative personal characteristics (Doris & Sarason 1955;I. Sarason & Glanzer 1962, 1963I. Sarason & Koenig 1965).…”
Section: The Problem Of Anxiety Anxiety: Its Nature and Importancementioning
confidence: 99%
“…Until recently the development of treatments for test anxiety largely ignored substantive research on cognitive processes. This research has shown that in evaluative situations test anxious individuals emit task-irrelevant, self-oriented responses (Liebert & Morris, 1967;Sarason & Ganzer, 1963;Sarason & Koenig, 1965). These self-oriented responses include worry about anticipated failure, preoccupation with feelings of inadequacy, and expectations of punishment.…”
Section: Introductionmentioning
confidence: 99%